2013
DOI: 10.7314/apjcp.2013.14.2.707
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Prognosis of Patients with Benign Thyroid Disease Accompanied by an Incidental Papillary Carcinoma

Abstract: Purpose: To investigate the clinical features and prognosis of papillary thyroid carcinoma (PTC) with a background of benign disease. Method: A total of 709 patients with papillary thyroid carcinoma undergoing surgical resection were analyzed retrospectively. In 147 patients who underwent surgery for benign thyroid disease, incidental PTC (IPC group) were identified by intraoperative or postoperative pathological examination of surgical specimens but were not detected by preoperative imaging studies. In the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Our analysis suggests that for male patients with younger age (<45 years old), more attention may be needed to be paid as the risk of LNM in this group of patients is high. There has been a major area of controversy that whether these sub-centimeter PTCs needed to be treated as crPTC4041. Some investigators advocated in favor of not performing further treatment in addition to initial thyroid surgery and some even suggest to remove the cancer label from indolent lesions242, whereas others suggested an aggressive surgical approach followed by radioiodine ablation therapy40.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis suggests that for male patients with younger age (<45 years old), more attention may be needed to be paid as the risk of LNM in this group of patients is high. There has been a major area of controversy that whether these sub-centimeter PTCs needed to be treated as crPTC4041. Some investigators advocated in favor of not performing further treatment in addition to initial thyroid surgery and some even suggest to remove the cancer label from indolent lesions242, whereas others suggested an aggressive surgical approach followed by radioiodine ablation therapy40.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also conform to the recent registry based studies from Finland (Hakala et al, 2012) and Wales (Amphlett et al, 2013); regarding the increasing trend of papillary carcinoma in Europe. Wang et al, (2013) in their study found incidental papillary carcinoma in 147 out of their 709 cases and concluded that these are more common in females.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis, the process of new blood vessel development, is crucial for further growth of the tumor, and local extension and metastasis of multiple tumor types such as thyroid carcinoma, breast cancer, and bladder cancer. [7][8][9] Microvessel density (MVD), a measure of tumor angiogenesis and a reference standard in the quantification of blood vessels, is an important prognostic factor associated with survival in patients with bladder cancer. 10 However, determining MVD requires surgical and biopsy specimens that are prone to sampling errors.…”
mentioning
confidence: 99%